2005
DOI: 10.1152/ajpregu.00532.2004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of selective and nonselective cyclooxygenase inhibitors on endothelin-1-induced fever in rats

Abstract: It was previously shown that sustained fever can be induced in rats by central injection of endothelin-1 (ET-1). This peptide appears to participate in the mechanism(s) of LPS-induced fever, which is reduced by pretreatments with ET B receptor antagonists. In this study, we compared the effects of a nonselective cyclooxygenase (COX) inhibitor, indomethacin, with those of two selective COX-2 inhibitors, celecoxib and lumiracoxib, on ET-1-induced fever in rats. Fever induced in conscious animals by ET-1 (1 pmol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
29
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 44 publications
6
29
0
5
Order By: Relevance
“…System). Preliminary experiments revealed that LPS-induced fever recorded using the radio-telemetry system was indistinguishable from that assessed by the rectal probe method [22].…”
Section: Clp Surgerymentioning
confidence: 91%
“…System). Preliminary experiments revealed that LPS-induced fever recorded using the radio-telemetry system was indistinguishable from that assessed by the rectal probe method [22].…”
Section: Clp Surgerymentioning
confidence: 91%
“…COX-2 is predominantly inducible under conditions of inflammation but basal levels of COX-2 are present in the brain (for a review, see Botting 2006). The use of selective COX-2 inhibitors (Cao et al 1997;Steiner et al 2001;Zhang et al 2003;Fabricio et al 2004) or of COX-2-deficient ("knockout") mice (Li et al 1999;Steiner et al 2005) suggest a critical role for COX-2 as a mediator of fever induced by bacterial LPS.…”
Section: Role Of Cox In Pipc-induced Fevermentioning
confidence: 99%
“…The proposal was supported by the fact that ICV administration of the selective ET B receptor antagonist BQ-788 substantially attenuates the fever induced by intravenous E. coli LPS, indicating that endogenous ETs contribute significantly to this response (7). Moreover, ICV ET-1 also causes a potent pyrogenic effect of ET-1 in the rat, which is fully prevented by prior ICV injection of the selective ET B receptor antagonist BQ-788 but is unaffected by the selective ET A receptor antagonist BQ-123 or prior systemic treatment with indomethacin (7,8). In contrast, fever induced by either ICV IL-1␤ or TNF-␣ is sensitive to inhibition by indomethacin but resistant to pretreatment with the ET B receptor antagonist (5,7).…”
mentioning
confidence: 99%